2018
DOI: 10.3390/ma11050723
|View full text |Cite
|
Sign up to set email alerts
|

Effect of DC Plasma Electrolytic Oxidation on Surface Characteristics and Corrosion Resistance of Zirconium

Abstract: Zr is a valve metal, the biocompatibility of which is at least on par with Ti. Recently, numerous attempts of the formation of bioactive coatings on Zr by plasma electrolytic oxidation (PEO) in solutions that were based on calcium acetate and calcium β-glycerophosphate were made. In this study, the direct current (DC) PEO of commercially pure zirconium in the solutions that contained Ca(H2PO2)2, Ca(HCOO)2, and Mg(CH3COO)2 was investigated. The treatment was conducted at 75 mA/cm2 up to 200, 300, or 400 V. Five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 80 publications
1
5
0
Order By: Relevance
“…The current research has shown the formation of a complex mesoporous coating in the ZrNb alloy using a Ca-P solution doped with CuNPs. Voltage control allows thick coatings with low Zr/Ca and Zr/P rates to be obtained with the 450 V mode, similar to other research reported with the formation of a PEO coating without NP addition [35]. We found a strong antibacterial effect of the CuNP-incorporated surface similar to the silver effect [36].…”
Section: Bacterial Adhesion Testsupporting
confidence: 88%
“…The current research has shown the formation of a complex mesoporous coating in the ZrNb alloy using a Ca-P solution doped with CuNPs. Voltage control allows thick coatings with low Zr/Ca and Zr/P rates to be obtained with the 450 V mode, similar to other research reported with the formation of a PEO coating without NP addition [35]. We found a strong antibacterial effect of the CuNP-incorporated surface similar to the silver effect [36].…”
Section: Bacterial Adhesion Testsupporting
confidence: 88%
“…In contrast, high current density had a harmful influence on the composition and attributes of the coating. Sowa et al [ 96 ] studied the influence of DC on the PEO coating of pure Zr in the presence of calcium acetate and calcium glycerol phosphate electrolytes. The process was carried out at 200, 300, and 400 V. It was observed that 200V resulted in the most corrosion-resistant coating without any porous structure.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma electrolytic oxidation (PEO) is an environmentally friendly surface treatment method that is successfully used to create wear-resistant, corrosion-resistant, heat-resistant, biocompatible and decorative coatings on aluminum, titanium, zirconium and other light alloys [1][2][3][4]. Unlike aluminum and titanium, zirconium alloys are less investigated in terms of the specific features of the PEO process mechanism; however, recent studies appear to be focused on Zr and its alloys [5][6][7]. One important Zr alloy application is nuclear fuel cladding which suffers from hydrogen embrittlement in the boiling water environment of a power plant [8,9]; the PEO coatings show a good promise for fuel cladding corrosion protection [10,11].…”
Section: Introductionmentioning
confidence: 99%